2018
DOI: 10.1111/jar.12459
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐assisted cognitive behavioural therapy: The experiences of adults who have an intellectual disability and anxiety or depression

Abstract: Combining technology with CBT is an effective way to reduce barriers to accessing mental health interventions and technology for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 17 publications
3
42
0
Order By: Relevance
“…When examining the ease-of-use of their intervention, they identified two design dilemmas concerning the need for repetition without losing user engagement, and how to incorporate different types of engagement. Meanwhile, Cooney and colleagues, extensively described participants' ability to engage with The Feel Good Island in terms of both mastery and struggle: participants reported gaining knowledge and understanding related to how to take better care of themselves or to develop more helpful coping strategies, but some required physical or cognitive support to complete the tasks (Cooney, Jackman, Tunney, Coyle, & O'Reilly, 2018). This maps well onto the perceived usefuleness and ease-of-use subthemes identified in our study.…”
Section: Interventions' End-userssupporting
confidence: 68%
“…When examining the ease-of-use of their intervention, they identified two design dilemmas concerning the need for repetition without losing user engagement, and how to incorporate different types of engagement. Meanwhile, Cooney and colleagues, extensively described participants' ability to engage with The Feel Good Island in terms of both mastery and struggle: participants reported gaining knowledge and understanding related to how to take better care of themselves or to develop more helpful coping strategies, but some required physical or cognitive support to complete the tasks (Cooney, Jackman, Tunney, Coyle, & O'Reilly, 2018). This maps well onto the perceived usefuleness and ease-of-use subthemes identified in our study.…”
Section: Interventions' End-userssupporting
confidence: 68%
“…Cooney and colleagues, extensively described participants' ability to engage with The Feel Good Island in terms of both mastery and struggle: participants reported gaining knowledge and understanding related to how to take better care of themselves or to develop more helpful coping strategies, but some required physical or cognitive support to complete the tasks (Cooney, Jackman, Tunney, Coyle, & O'Reilly, 2018). This maps well onto the perceived usefuleness and ease-of-use subthemes identified in our study.…”
Section: Interventions' End-userssupporting
confidence: 67%
“…Of course, one type of intervention may never fit all. In all studies reported so far, some participants reported feeling left out, being unable or unwilling to engage with the intervention, or needing more sessions or support (Cooney et al, 2018;Vereenooghe & Westermann, 2019b). Fortunately, participants are generally eager to suggest ways to improve user engagement and understanding.…”
Section: Supported-interventions: Facilitating Conversations and Allimentioning
confidence: 99%
“…Recent studies examining mobile assistive technology for people with ID also highlight the importance of training for users and/or the presence of ongoing support from a significant other [44,45]. Other research into e-mental health for people with ID has focused on the use of computerized therapy with psychologists [17,30]. When a platform such as Healthy Mind is intended to be used without the direct assistance of a counselor or psychologist, it is important to consider how linking in with other existing services may ensure that users are supported to engage with the program in a way that best suits their needs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no research has examined the design of e-mental health platforms for people with an ID. Nevertheless, Cooney et al’s [30] qualitative study of the experience of participants in the Pesky Gnats randomized controlled trial highlighted some elements of program design, from the use of images to the delivery of a workbook, that affected participants’ engagement with the program.…”
Section: Introductionmentioning
confidence: 99%